Promoting Multicultural Awareness In Social Studies At Madrasah Ibtidaiyah - Muqarramah Sulaiman Kurdi (Badan Penerbit STIEPARI Press, 2023)
This study explores the strategies and approaches used to promote multicultural awareness in Social Studies at Madrasah Ibtidaiyah and examines their effectiveness in fostering intercultural understanding among students. It also addresses the key challenges and barriers faced by teachers in integrating multicultural perspectives into the curriculum and suggests strategies to overcome these obstacles. Furthermore, the research investigates the extent to which the inclusion of multicultural content in social studies contributes to students' cultural competence and empathy towards diverse cultures and religions. The research methodology employed is library research, utilizing a descriptive analytic approach. The findings of the research indicate that various strategies, such as incorporating diverse literature, utilizing inclusive teaching methods, engaging in intercultural dialogue, and involving the local community, effectively promote multicultural awareness in Social Studies at Madrasah Ibtidaiyah. These recommendations encompass establishing a supportive school culture, integrating multicultural perspectives across the curriculum, engaging with local communities, and implementing ongoing evaluation and assessment. This research emphasizes the significance of promoting multicultural awareness in Social Studies at Madrasah Ibtidaiyah.